Redox- and pH-responsive block copolymer nanocarriers with dual drug conjugation through dynamic covalent and hydrogen bonds - Avhad, Shankarrao V.; Surapaneni, Sai Geetika; Purohit, Poorvi M.; Ambade, Ashootosh V. (Journal of Applied Polymer Science, 2026)
Loading of multiple drugs in a nanocarrier with high entrapment efficiency is important for combination therapy in cancer treatment. Here, a block copolymer comprising hydrophobic poly(epsilon-caprolactone) block with a defined number of pendent propargyl groups, polyethylene glycol monomethyl ether as a hydrophilic block, and a redox-responsive disulfide group at the block junction is synthesized using click chemistry and ring-opening polymerization (ROP). Benzaldehyde and thymine groups are introduced in the side chains for selective attachment of anti-cancer drugs, doxorubicin (DOX) and methotrexate (MTX), via the formation of pH-responsive imine linkage and hydrogen bonds, respectively. The drug-conjugated block copolymers are assembled into spherical micelles of < 200 nm, and the preferential release of DOX and MTX in response to acidic pH and redox conditions is shown. At pH 5, DOX release was 59.5%, and MTX release was 40% compared to 13% and 12% at pH 7.4, whereas at pH 5 with 10 mM GSH, a DOX release of 81.5% was observed after 48 h. Cellular uptake of drug-conjugated micelles and their apoptosis compared to free DOX in the MDA-MB-231 breast cancer cells is demonstrated. Caveolae-mediated endocytosis was found to be the major pathway used by drug-loaded nanocarriers.
Keywords: biodegradable; copolymers; DOX-conjugate; drug delivery systems; methotrexate; micelles; pH-responsive; redox-responsive